2002
DOI: 10.1074/jbc.m204463200
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Mediates Age-associated Increase in Macrophage Cyclooxygenase-2 Expression

Abstract: Previously, we showed that macrophages (MØ) from old mice have significantly higher levels of lipopolysaccharide (LPS)-induced prostaglandin E 2 (PGE 2 ) production than young mice, due to increased cyclooxygenase-2 (COX-2) mRNA levels. The aim of the current study was to determine the underlying mechanisms of ageassociated increase in COX-2 gene expression. The results demonstrate that increased COX-2 mRNA expression in the old mice is due to a higher rate of transcription rather than increased stability of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 60 publications
2
48
0
Order By: Relevance
“…Finally, blocking NF-B activation reduced LPS-stimulated IL-6 and TNF-␣ production and SMaseinduced IL-6 production. Increased tissue ceramide content with aging has been reported (32)(33)(34)(35), but the mechanism underlying this phenomenon remains elusive. Cellular ceramide can be generated through the hydrolysis of sphingomyelin catalyzed by SMase or its de novo synthesis under action of several enzymes, including the rate-limiting SPT, from palmitoyl CoA and serine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, blocking NF-B activation reduced LPS-stimulated IL-6 and TNF-␣ production and SMaseinduced IL-6 production. Increased tissue ceramide content with aging has been reported (32)(33)(34)(35), but the mechanism underlying this phenomenon remains elusive. Cellular ceramide can be generated through the hydrolysis of sphingomyelin catalyzed by SMase or its de novo synthesis under action of several enzymes, including the rate-limiting SPT, from palmitoyl CoA and serine.…”
Section: Discussionmentioning
confidence: 99%
“…Because insulin resistance sharply increases with advancing age and low-grade inflammation in adipose tissue plays a key role in the development of insulin resistance, we hypothesized that aging is associated with increased adipose tissue inflammation. Furthermore, because both ceramide and NF-B are implicated in insulin resistance in insulin target cells as well as in age-associated up-regulation of inflammatory responses (19,(32)(33)(34)(35)(36)(37)(38)(39)(40), we conducted experiments to determine the role of ceramide and NF-B in age-associated adipose tissue inflammation.…”
mentioning
confidence: 99%
“…Our recent study showed that the intracellular concentration of ceramide was higher in LPS-stimulated M of old mice compared with those of young mice and that this increased level of ceramide mediates the age-associated up-regulation of COX-2 transcription (14). Whereas the effect of ceramide on regulation of transcription factors has not been well defined, previous studies showed that ceramide induced AP-1 (28) and NFB activation (29).…”
mentioning
confidence: 96%
“…This increased COX activity is, in turn, a result of increased expression of COX-2 protein and mRNA (13). In a recent study, we further demonstrated that the age-related increase in COX-2 mRNA was because of a higher level of ceramide in old M compared with those of young, which induced up-regulation of COX-2 transcription (14). In addition, we showed that the effect of ceramide was not mediated through components of the mitogen-activated protein kinase pathway, c-Jun NH 2 -terminal kinase, extracellular signal-regulated kinase, or p38 (14).…”
mentioning
confidence: 99%
“…[6][7][8] Peritoneal macrophages, hepatocytes, and glial cells isolated from aged animals exhibit more severe and prolonged responses to inflammatory challenges compared with cells originating from young animals. [6][7][8][9] This hyperresponsiveness is manifested in altered activation patterns of cyclooxygenase-2, c-jun N-terminal kinase (JNK), nuclear factor kappa-B, CCAAT/enhancer binding protein alpha, and CCAAT/enhancer binding protein beta. Hence, changes in the cellular signaling pathways may contribute to the onset of the pro-inflammatory state in aging.…”
mentioning
confidence: 99%